Patterns of skin cancer and treatment outcomes for patients with albinism at Kisangani Clinic, Democratic Republic of Congo. (12th June 2020) - Inena, Gaylord; Chu, Brian; Falay, Dadi; Limengo, Bambale; Matondo, Ibanda; Bokanga, Abisa; Kovarik, Carrie; Williams, Victoria L.
Abstract: Background: People with albinism (PWA) are at increased risk of photodamage and skin cancer. In many parts of Africa, there is a significant lack of knowledge regarding albinism which can lead to societal stigma, discrimination, and persecution from an early age. In the Democratic Republic of Congo (DRC), there is limited clinical data on PWA and skin cancer. We aim to better understand sociodemographics, risk factors, clinical features, and outcomes of this population. Methods: Patients with a diagnosis of albinism and skin cancer presenting to Kisangani Albino Clinic were enrolled. Results: Of 205 PWA, 61 patients were diagnosed with skin cancer with a mean age of 26.5 years. Common occupations were student (45.6%) or unemployed (26.4%). Discrimination was experienced from close contacts (24.4%) and society (67.4%). A majority (88.5%) had never used sunscreen, only 4.9% used fully sun protective clothing, and 90.2% spent 4 or more hours in the sun daily. Skin cancers had a mean size of 3.8 cm and were most commonly located on the face (47.7%). Squamous cell carcinoma was the most common histopathological diagnosis. Most patients underwent excision, and 90.2% had clinical clearance of tumors at a mean follow‐up of 5.7 months. Conclusion: People living with albinism in the DRC experience a high rate of nonmelanoma skin cancers at a young age and additionally face a number of psychosocial challenges. This study represents the first attempt to analyze a cohort of patients with albinism from the DRC and serves to increase awareness of this vulnerable population.